Biobased and biodegradable films exhibiting circularly polarized room temperature phosphorescence - Mengnan Cao; Yiran Ren; Yue Wu; Jingjie Shen; Shujun Li; Zhen-Qiang Yu; Shouxin Liu; Jian Li; Orlando J. Rojas; Zhijun Chen (Nature Communications, 2024)
Abstract There is interest in developing sustainable materials displaying circularly polarized room-temperature phosphorescence, which have been scarcely reported. Here, we introduce biobased thin films exhibiting circularly polarized luminescence with simultaneous room-temperature phosphorescence. For this purpose, phosphorescence-active lignosulfonate biomolecules are co-assembled with cellulose nanocrystals in a chiral construct. The lignosulfonate is shown to capture the chirality generated by cellulose nanocrystals within the films, emitting circularly polarized phosphorescence with a 0.21 dissymmetry factor and 103 ms phosphorescence lifetime. By contrast with most organic phosphorescence materials, this chiral-phosphorescent system possesses phosphorescence stability, with no significant recession under extreme chemical environments. Meanwhile, the luminescent films resist water and humid environments but are fully biodegradable (16 days) in soil conditions. The introduced bio-based, environmentally-friendly circularly polarized phosphorescence system is expected to open many opportunities, as demonstrated here for information processing and anti-counterfeiting.